STUDENTS' STRATEGIES IN TRANSLATING AN ENGLISH TEXT INTO BAHASA INDONESIA : A case study at the English Education Department of FPBS UPI Bandung - Ahmad, Mahdi (2012)
This case study investigated translators' translation strategies or procedures, problems and solutions in translating an English text into bahasa Indonesia. The study involved six English students of the seventh semester at English program FPBS of UPI. A qualitative approach, particularly descriptive study, was employed in this study, with two data collection techniques: documentation and interview. The analysis of students' strategies in translation used the theory from Vinay and Darbelnet (in Munday, 2001; in Venuti, 2004) and Newmark (1988). This analysis mainly focused to answer the research question about the procedures applied by the students in their translations. Meanwhile, the data from interviews were analyzed to discuss the problems encountered by the students in translating the task and also the solutions they used in handling the problems. The study revealed that the students employed sevenne procedures of translation from Vinay and Darlbelnet (1965) and Newmark (1988) to translate the units of the text, that are Shift or Transposition (20.6%), Couplet (18.83%), Literal translation (15%), Borrowing or Transference (12.5%), Reduction (12%), Expansion (10.16%), Paraphrase (6%), Naturalization (3.83%), and Modulation (0.16%). There were similar units translated with the same strategies, and some were translated with different strategies. It was also found that the students encountered difficulties in lexical aspect in doing translation. The difficulties were caused by the limitation of students' competences. Besides the different strategies applied for the same units of text, the students also had different ways to solve the same problems they deal with in their translation activity.